The Legal status of international treaties in the Jordanian constitution and judiciary - Abuazzam, Saddam Ibrahim Abdulkhaliq (Journal of Economic, Administrative and Legal Sciences, 2021)
This descriptive analytical legal study aimed to clarify the position of international treaties in the Jordanian constitution and judiciary by shedding light on the theoretical trends that determined the status of international treaties in comparative legislation, in addition to verifying the constitutionality of the Jordanian side's signature on some international treaties that occupied Jordanian public opinion. The study revealed that the difference of international law jurists in determining the legal status of international treaties in constitutions and positive laws resulted in three directions: the trend of the unity of the two laws, the trend of the Dual-law, and the trend of reconciling the two laws. The study also showed that the Jordanian constitution did not adopt an explicit provision for the legal status of treaties. International conventions, leaving room for jurisprudential and judicial jurisprudence that affirmed the supremacy of international treaties over domestic law. The study also found that the Jordanian legislator’s neglect of determining the legal status of treaties, and the double signature of them by the executive authority alone or in combination with the legislative authority in accordance with two conditions under Paragraph B of Article 33 of the Jordanian Constitution, has opened the door wide for controversy over any treaty to be signed by the Jordanian side, To demonstrate this, the study mentioned practical applications from international treaties signed by Jordan, namely: the Israeli Gas Supply Agreement, the Casino Agreement, and the CEDAW Agreement. In light of the results were reached, the study presented a set of recommendations that were such as issuing a law for international treaties to regulate international treaties in all the stages through which they pass, adding a constitutional text confirming the oversight role of the National Assembly over international treaties, provided that this constitutional text includes informing the National Assembly of any treaty or agreement that is concluded by Jordan.
Keywords: international treaties; international law; the Jordanian constitution; national law; casino agreement; CEDAW agreement; gas agreement